Transfer Pricing: Tunnelling Incentive dan Tax Haven Dimoederasi Foreign Ownership - Sari Apriliyani; Jobelina Jelma Ribeiro Soares (Yayasan Literasi Ilmiah Indonesia, 2024)
Purpose: The purpose of this study is to determine the effect of tunnelling incentive and tax haven on transfer pricing and to determine the effect of foreign ownership in strengthening or weakening the relationship of tunnelling incentive and tax haven on transfer pricing. Method: This study uses purposive sampling method, the population used is manufacturing companies listed on the IDX from 2020 to 2022 with a total sample of 492 companies and 123 data analysis was selected. This research technique uses multiple linear regression analysis techniques. Findings: The results showed that tunneling incentive and tax haven negatively affect transfer pricing. Moderating variable, foreign ownership can strengthen the relationship of tunneling to transfer pricing but fails to strengthen the relationship of tax haven to transfer pricing.